Masculinization By Using Method Of The Immersion And Oral To Genital Change Of Tilapia Oerochromis niloticus - Mangaro, Ramlesius; Sinjal, Hengky J.; Monijung, Revol D. (Jurnal Ilmiah PLATAX, 2018)
This research activity was conducted at Balai Pembenihan, Pengendalian Hama dan Penyakit Tateli from August -September 2017. The treatment in this study was masculinization by using Immersion Method (P), Oral (O) and Control or without hormone addition (K). In the method of immersion with a dose of 10 mg / L water / 100 larvae in soak for 6 hours. Oral Method with a dose of 15 mg / kg of feed hormone, administration for 14 days. Control is maintenance without treatment. The result of male sex test identification at the end of the experiment was obtained by the percentage of males after the highest treatment was Oral (O) treatment of 92.57%, the immersion treatment (P) of 89.53%, and the last was Control (K) , 73%. The survival rate (SR) of the test fish during the 50 days of trial maintenance was highest in Oral test fish, 61.67% followed by Immersion 53% and 38.67% Control. Keywords : Fish,  Immersionn, Masculinization, Oral, Survival, TilapiaAbstrakPenelitian ini dilakukan di Balai Pembenihan, Pengendalian hama dan Penyakit Tateli dari bulan Agustus – September 2017.  Perlakuan dalam penelitian ini adalah maskulinisasi dengan menggunakan metode Peredaman (P), Oral (O) dan Kontrol atau tanpa penambahan hormon (K). Pada metode Perendaman dengan dosis 10 mg/L air/100 ekor larva di rendam selama 6 jam. Metode Oral dengan dosis hormon 15 mg/Kg pakan, pemberian selama 14 hari. Kontrol adalah pemeliharaan tanpa perlakuan. Hasil identifikasi kelamin jantan ikan uji pada akhir percobaan didapat persentase jantan setelah perlakuan tertinggi adalah perlakuan Oral (O) sebesar 92,57 %, perlakuan Perendaman (P) sebesar 89,53 %, dan yang terakhir adalah Kontrol (K) dengan hasil sebesar 52,73 %. Persentase kelangsungan hidup (SR) ikan uji selama pemeliharaan 50 hari percobaan adalah yang tertinggi terdapat pada ikan uji Oral  yaitu sebesar 61,67%  diikuti dengan Perendaman sebesar 53 % dan Kontrol sebesar 38,67  %.Kata kunci : Ikan, Maskulinisasi, Perendaman, Oral, Kelangsungan Hidup, Nila